MANAGEMENT FOR IMPROVING THE QUALITY OF LECTURER IN RESEARCH AT UNIVERSITIES - Sujudi, Nayyif; Gaffar, Mohammad Fakry; Komariah, Aan; Kurniady, Dedy Achmad (Jurnal Administrasi Pendidikan, 2024)
This study is focused on examining the management of improving the quality of lecturers in research at universities. The research method used is descriptive qualitative in Private Universities in Bandung involving respondents from university leaders, the Directorate of PPM, deans, study programs and lecturers. The results of the research show that the implemented policy becomes an element of determination in managerial aspects of safety in terms of success targets, research evaluation, and research. In the aspect of personal management, research development is carried out for lecturers capable of making proposals, attending scientific forums nationally and internationally and providing research incentives and scientific publications. While in the managerial aspects of society, the improvement of the quality of lecturers in research is designed as a form of contribution to solving problems in the community which is an emphasis on improving the ability of lecturers to conduct research.